Answer:
m - n = 501
Explanation:
Remark
The first thing you have to do is find the number of odd and even numbers. This is where you have to be careful because there is a danger of being out by one.
equation
l = a + (n - 1)*d
Solution even
l = 1000
a = 2
d = 2
1000 = 2 + (n - 1)*2
998/2 = (n - 1) * 2 / 2
499 = n - 1
n = 500
Solution odd
l = 1001
a = 1
d = 2
1001 = 1 + (n - 1)*2
1000 = (n - 1)*2
1000/2 = (n - 1)2/2
500 = n - 1
501 = n
Sum Even of even numbers from 1 to 1001
Givens
a = 2
n = 500
l = 1000
Equation
Sum = (a + l ) * n / 2
Solution
Sum = (2 + 1000)*500/2
Sum = 1002 * 250
Sum = 250500
Sum of Odd numbers from 1 to 1001
a = 1
l = 1001
n = 501
Equation
sum = (a + l)*n/2
sum = (1 + 1001) * 501
sum = (1002)*501 / 2
Sum = 251001
Answer
m - n = 251001 - 250500 = 501